Application of low-intensity pulsed ultrasound on tissue resident stem cells: Potential for ophthalmic diseases - Lin, Zichun; Gao, Liyu; Hou, Ning; Zhi, Xushuang; Zhang, Yupeng; Che, Zelin; Deng, Aijun (Frontiers in Endocrinology, 2023)
Introduction Tissue-resident stem cells (TRSCs) have the ability to self-renew and differentiate throughout an individual’s lifespan, and they utilize both mechanisms to maintain homeostasis and regenerate damaged tissues. Several studies suggest that these stem cells can serve as a potential source for cell-replacement-based therapy by promoting differentiation or expansion. In recent years, low-intensity pulsed ultrasound (LIPUS) has been demonstrated to effectively stimulate stem cell proliferation and differentiation, promote tissue regeneration, and inhibit inflammatory responses. Aims To present a comprehensive overview of current application and mechanism of LIPUS on tissue resident stem cells. Methods We searched PubMed, Web of Science for articles on the effects of LIPUS on tissue resident stem cells and its application. Results The LIPUS could modulate cellular activities such as cell viability, proliferation and differentiation of tissue resident stem cells and related cells through various cellular signaling pathways. Currently, LIPUS, as the main therapeutic ultrasound, is being widely used in the treatment of preclinical and clinical diseases. Conclusion The stem cell research is the hot topic in the biological science, while in recent years, increasing evidence has shown that TRSCs are good targets for LIPUS-regulated regenerative medicine. LIPUS may be a novel and valuable therapeutic approach for the treatment of ophthalmic diseases. How to further improve its efficiency and accuracy, as well as the biological mechanism therein, will be the focus of future research.